A Multiproduct Cost Study of Savings and Loans - MESTER, LORETTA J. (Journal of Finance, 1987)
ABSTRACT This paper investigates the cost structure of savings and loans. Most studies of financial institutions have failed to take into account the multiproduct nature of these institutions. Using the multiproduct approach, the existence of subadditivity, multiproduct global and product‐specific economies of scale and scope, and substitutability between inputs is investigated. A translogarithmic cost function is estimated using 1982 data on California savings and loans. Restrictive functional forms also estimated are rejected. Standard errors for the statistics calculated are estimated, and various statistical tests are conducted. Previous authors have not calculated standard errors for these statistics. No evidence of subadditivity in the industry is found.